Current state of MRI of the fetal brain in utero. Issue 3 (24th October 2018) - Jarvis, Deborah A.; Griffiths, Paul D.
Abstract : In this article we provide an overview of fetal brain development, describe the range of more common fetal neuropathology, and discuss the relevance of in utero MR (iuMR). Although ultrasonography remains the mainstay of fetal brain imaging, iuMR imaging is both feasible and safe, but presents several challenges. We discuss those challenges, the techniques employed to overcome them, and new approaches that may extend the clinical applicability of fetal iuMR. Level of Evidence: Technical Efficacy Stage. J. Magn. Reson. Imaging 2019;49:632–646.